Compressive Strength and Physical Properties Behavior of Cement Mortars with addition of Cement Klin Dust (Journal of University of Babylon for Engineering Sciences, 2017)
Cement Klin Dust (CKD) was the waste of almost cement industry factories, so that in this paper utilization of CKD as filler in cement and/or concrete was the main objective. CKD from the Karbala cement factory had been used and analysis to know the chemical composition of the oxides was done. In this paper cement mortars with different weight percentages of CKD (0,5,10,20,30,40) had been prepared. Physical properties such as density and porosity were done in different age curing (3, 7, 28) day. In addition, mechanical properties included the coefficient of thermal conductivity and compressive strength had also observed with different age (3,7, and 28) for all prepared specimens. From the obtained the experimental results and their discussion, it was clear that the addition (20%) of CKD had the good results in cement mortars.